Does Spinal Fusion and Scoliosis Correction Improve Activity and Participation for Children With GMFCS level 4 and 5 Cerebral Palsy?. Issue 49 (December 2015) - Sewell, Mathew David; Wallace, Charlie; Malagelada, Francesc; Gibson, Alex; Noordeen, Hilali; Tucker, Stewart; Molloy, Sean; Lehovsky, Jan
Abstract : Abstract: Spinal fusion is used to treat scoliosis in children with cerebral palsy (CP). Following intervention, the WHO considers activity and participation should be assessed to guide intervention and assess the effects. This study assesses whether spinal fusion for scoliosis improves activity and participation for children with severe CP. Retrospective cohort study of 70 children (39M:31F) with GMFCS level 4/5 CP and significant scoliosis. Thirty-six underwent observational and/or brace treatment as the sole treatment for their scoliosis, and 34 underwent surgery. Children in the operative group were older and had worse scoliosis than those in the observational group. Questionnaire and radiographic data were recorded over a 2-year period. The ASKp was used to measure activity and participation. In the observational group, Cobb angle and pelvic obliquity increased from 51 o (40–90) and 10 o (0–30) to 70 o (43–111) and 14 o (0–37). Mean ASKp decreased from 16.3 (1–38) to 14.2 (1–36). In the operative group, Cobb angle and pelvic obliquity decreased from 81 o (50–131) and 14 o (1–35) to 38 o (10–76) and 9 o (0–24). Mean ASKp increased from 10.5 (0–29) to 15.9 (3–38). Spinal-related pain correlated most with change in activity and participation in both groups. There was no difference in mobility, GMFCS level, feeding or communication in either group before and after treatment. In children with significant scoliosis and CP classified within GMFCS levels 4 and 5, spinal fusion was associated with an improvement in activity and participation, whereas nonoperative treatment was associated with a small reduction. Pain should be carefully assessed to guide intervention.